(untitled) (Singaporean Journal of Business Economics and Management, 2020)
It is known that Ethiopia has been working to join countries of middle-income economy in the coming decades. Having this in mind, participating youth entrepreneurs in the economy play a great role. Since the general objective of the study is to assess factors affecting youth intention towards entrepreneurship in south Gondar zone selected woredas. The study employed explanatory research design and both qualitative and quantitative type of data was used for the purpose of the study. To collect primary data, structured questionnaire was designed and collected through based on the random selection by using lottery method. Structured questionnaires were distributed to 398 customers, only 329 complete responses were returned from the customers. The SPSS version 20 was use as a tool to process the primary data which is collected through questionnaire. The result of the study indicated that, Only 27.8% of the variation of dependent variable (youth entrepreneurial intention) can be explained by the five independent variables (Social norm, Perceived access for finance, Perceived government policy, entrepreneurial education & family background). The overall regression model for these five predictors has significantly explained the variation on youth’s entrepreneurial intention. Based on the findings of the study, the researcher gives some recommendations includes significant difference in entrepreneurial intention was found between youths of business family background and non business family background. Non business family background students have lower entrepreneurial intention than business family background students. Therefore, Specific intervention program such as seminars and experience sharing program should be done to improve entrepreneurial intention among non business family students.